Effects of respiratory exercises on pulmonary function of chemically afflicted soldiers in Khoramabad - Ghahri Sarabi, A; Heydarizadeh, Kh; Barahimi, N; Alavi Majd, H; Yaghmaei, F (Advances in Nursing & Midwifery, 2008)
Background Following an extensive use of chemical weapons in imposed war of Iran, many known and unknown complications in different body systems particularly respiratory tract have been reported. To treat pulmonary complication of afflicted soldiers, different measures such as drug as well as oxygen therapy and rehabilitation are performed. Purpose This clinical trial was conducted to identify the effects of respiratory exercises (pursed lip and diaphragmatic breathing) on pulmonary function of chemically afflicted soldiers in Khoramabad in 2002. Methods 68 soldiers with respiratory problems were randomly selected and divided in two experimental and control groups. They were matched in terms of age, body mass index, chemical gas type, duration of contact, number of hospitalization, type of cough, forced vital capacity indices, forced expiratory volume in 1 second and …. Spirometry was used to monitor pulmonary function. The experimental group performed the exercises 15 minutes a day over 10 days. The indices were measured again after 10 days. A questionnaire, an assessment form for dyspnea severity and a special form for classifying the result of pulmonary function tests (PFT) were used for data collection. Results Findings showed a significant difference between the means of PFTs before and after the intervention in the experimental group and no difference in the control group. A significant difference was also found in the mean percentage of dyspnea severity reduction between the two groups before and after the intervention (P=0.000). Conclusion According to the results, pursed lip as well as diaphragmatic breathing would improve pulmonary function indices in spirometry and dyspnea severity would significantly decrease, which is similar to other studies. Keywords Pulmonary exercise, Pursed lip breathing, diaphragmatic breathing, Pulmonary function, chemically afflicted soldier